Cold energy utilization of liquefied natural gas for capturing carbon dioxide in the flue gas from the magnesite processing industry. (15th June 2016) - Zhao, Liang; Dong, Hui; Tang, Jiajun; Cai, Jiuju
Abstract: In the present paper, a novel system based on LNG (liquefied natural gas) cold energy utilization was proposed to capture CO2 in the exhaust gas discharged from the magnesite processing industry located in Liaoning Province (China). The system also combined with a twin-stage ORC (organic Rankine cycle) power generation sub-system using LNG as heat sink and exhaust gas as heat source. Based on the exergy analysis method, the LNG regasification pressure and the CO2 capture pressure were investigated as the key operation parameters to find the suitable working conditions of the system. The results show that, in Liaoning Province, the amount of LNG cold energy received at Xianrendao Port can theoretically afford to capture CO2 in the exhaust gas from the magnesite processing industry at Dashiqiao Area. In addition, when the LNG regasification pressure and the CO2 capture pressure is respectively set as 1.0 MPa and 0.15 MPa, the system can reach exergy efficiency of 0.57 and provide 119.42 kW electric power and 0.75 t liquid CO2 per ton LNG. For downstream utilization of CO2, a CO2 utilization sub-system was proposed. It integrates Rankine cycle, water electrolysis and carbon dioxide hydrogenation for methanol production by solar energy and liquefied CO2 cold energy utilization. Highlights: We propose a system based on the LNG cold energy utilization for capturing CO2 . The two key operation parameters of the system have been investigated. The maximum network output of the system is 119.42 kW under the specific condition. A potential CO2 utilization subsystem is proposed for methanol production.